Transitoriedade inflamável : sentidos subjetivos da participação no trabalho no posto de combustível Vila Velha - André, Ingrid Dias Barreto (2011)
This paper addresses the topic work participation under the Private Administration. The concept of participation adopted involves decisions that relate to the plan to achieve the mission and the collective goals of the organization, whether corporate or n